Short-term Results of Hemiarthroplasty of the Ankle Joint for Talar-Sided Cartilage Loss - Manuel J. Pellegrini MD; Franco Mombello MD; Aaron Cortes PhD; Felipe Chaparro MD; Cristian Ortiz MD; Giovanni Carcuro MD (Foot & Ankle Orthopaedics, 2023)
Background: Ankle hemiarthroplasty is a 1-piece implant system replacing the talar side of the tibiotalar joint. Hemiarthroplasty offers limited bone resection and may provide easier revision options than joint-ablating procedures. Methods: Prospective, multicenter, noncomparative, nonrandomized clinical study with short term follow-up on patients undergoing hemiarthroplasty of the ankle. Radiologic and functional outcomes (Foot and Ankle Outcome Score FAOS, Foot and Ankle Ability Measure [FAAM], Short Form–36 Health Survey [SF-36], Short Musculoskeletal Functional Assessment [SMFA], and visual analog scale [VAS] pain scores) were obtained at 3 and 12 months and the last follow-up (mean 31.9 months). Results: Ten patients met the inclusion criteria. Three were converted to total ankle replacement at 14, 16, and 18 months. Pain VAS scores improved on average from 6.8 to 4.8 ( P  = .044) of the remaining 7 at a mean of 31.9 months’ follow-up. For these 7 in the Survival Group, we found that SF-36 physical health component improved from 25.03 to 42.25 ( P  = .030), SMFA dysfunction and bother indexes improved from 46.36 to 32.28 ( P  = .001), and from 55.21 to 30.14 ( P  = .002) in the Survival Group, and FAAM sports improved from 12.5 to 34.5 ( P  = .023). Conclusion: Patients undergoing hemiarthroplasty of the ankle joint for talar-sided lesions had a 30% failure rate by 18 months. Those who did not have an early failure exhibited modest pain reduction, functional improvements, and better quality of life in short-term follow-up. This procedure offers a possible alternative for isolated talar ankle cartilage cases. Level of Evidence: Level IV, prospective case series.